Magnitude of Gender-Based Violence and Its Associated Factors among Female Night Students in Bahir Dar City, Amhara Region, Ethiopia - Belay, Habtamu Gebrehana; Liyeh, Tewachew Muche; Tassew, Habtamu Abie; Ayalew, Abeba Belay; Goshu, Yitayal Ayalew; Mihretie, Gedefaye Nibret (International Journal of Reproductive Medicine, 2021)
Background. Gender-based violence (GBV) is a major public health issue that affects the health and well-being of millions of young people worldwide each year. Gender-based violence was prevalent throughout Sub-Saharan Africa. However, research in Africa is extremely diverse. Objective. The purpose of this study is to determine the extent and risk factors of gender-based violence among night female students in Bahir Dar, Ethiopia. Methods. This cross-sectional study was conducted among 788 elementary and high school night female students in Bahir Dar from October 15 to November 15, 2019. Data was gathered using self-administered questionnaires. A binary and multiple logistic regression model was used to identify factors associated with gender-based and sexual violence. An adjusted odds ratio (AOR) with a 95 percent confidence interval (CI) was calculated to determine the level of significance. Results. The overall lifetime prevalence of gender-based violence (sexual, physical, and emotional violence) was 71.1% with a 95% CI of 67.8%-74.1%. The lifetime prevalence of sexual violence, physical violence, and emotional violence was 49.1%, 57.5%, and 41.6%, respectively. Rural childhood residence (AOR: 3.37, 95% CI: (2.17-5.54)), low school performance (AOR: 3.44, 95% CI: (2.13-5.56)), lack of sexual and reproductive health conversation experience (AOR: 3.68, 95% CI: (2.07-6.54)), poor family control (AOR: 5.62, 95% CI: (3.25-9.71)), and being sexually active (AOR: 3.79, 95% CI: (2.35-6.12)) increased significantly the risk of gender-based violence. The risk factors for sexual violence were young people living with both parents (AOR: 0.28, 95% CI: (0.19-0.41)), peer pressure (AOR: 5.73, 95% CI: (4.11-7.98)), and family support (AOR: 0.31, 95% CI: (0.22-0.43)). Conclusion. In the study area, the lifetime prevalence of sexual violence, physical violence, and emotional violence was high. As a result, it is recommended that policymakers, district officials, schools, and other stakeholders pay attention to and act on gender-based values.